The Role Of Clinical Nurse Specialists As Clinical Leaders And Their Perceived Contributions To Quality Of Care And Patient Safety: A Descriptive Study - Ediansyah, Ediansyah; Pertiwi, Retno Indah; Nitzah, Nitzah; Azzhara, Fia; Nawangwulan, Rahayu (Universitas Islam Negeri Alauddin Makassar, 2026)
Background: Clinical Leadership (CL), carried out by Clinical Nurse Specialists (CNS), plays a crucial role in improving the quality of care and patient safety through their clinical knowledge and experience. Evaluation of the CNS's role from a peer perspective is necessary to assess the effectiveness of their contribution to healthcare. This study aims to describe the role of the CNS as a CL based on the perspectives of the CNS, Professional Care Providers (PPA), and management at AN-NISA Hospital, Tangerang. Methods: This research uses a descriptive quantitative approach involving 177 respondents to find out the perceptions between CNS, PHCP, and management regarding CNS leadership practices. Results: The results of the input aspect of the study indicate that the CNS is ready to implement organizational strategies, address healthcare gaps (M=4.63), understand the necessary structure and workflow (M=4.43), and possess leadership competencies (M=4.06). However, the results of the process and output aspects of the study indicate a gap between the perspectives of the CNS, PHCP, and management. The CNS felt they had not yet engaged in providing support to their colleagues (M=3.55), while PHCP assessed that the CNS were sufficiently involved in providing support to their colleagues (M=4.19). Another gap can be seen in the output aspect, where PHCP felt satisfied with the presence of the CNS, while the CNS felt that their colleagues were not satisfied with their performance results. One factor that can cause tension is reduced trust in the CNS. Conclusion: The CNS performance process and results show that CNS has the ability to carry out its role as a CL. CNS can improve patient outcomes by focusing on their roles and responsibilities, PHCP increasing support and collaboration with CNS, and management providing support to CNS to increase confidence